Methanol Extract of Ocimum Gratissimum Protects Murine Peritoneal Macrophages from Nicotine Toxicity By Decreasing Free Radical Generation, Lipid and Protein Damage and Enhances Antioxidant Protection. Issue 4 (2009) - Mahapatra, Santanu Kar; Chakraborty, Subhankari Prasad; Das, Subhasis; Roy, Somenath
Abstract : In the present study, methanol extract of Ocimum gratissimum Linn (ME-Og) was tested against nicotine-induced murine peritoneal macrophage in vitro. Phytochemical analysis of ME-Og shown high amount of flavonoid and phenolic compound present in it. The cytotoxic effect of ME-Og was studied in murine peritoneal macrophages at different concentrations (0.1 to 100 µg/ml) using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide (MTT) method. To establish the protective role of ME-Og against nicotine toxicity, peritoneal macrophages from mice were treated with nicotine (10 mM), nicotine + ME-Og (1 to 25 µg/ml) for 12 h in culture media. The significantly (p < 0.05) increased super oxide anion generation, reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity, myeloperoxidase (MPO) activity, lipid peroxidation, protein carbonyls, oxidized glutathione levels were observed in nicotine-treated group as compared to control group; those were significantly (p < 0.05) reduced in ME-Og supplemented groups in concentration dependent manner. More over, significantly (p < 0.05) reduced antioxidant status due to nicotine exposure was effectively ameliorated by ME-Og supplementation in murine peritoneal macrophages. Among the different concentration of ME-Og, maximum protective effect was observed by 25 µg/ml, which does not produce significant cell cytotoxicity in murine peritoneal macrophages. These findings suggest the potential use and beneficial role of O. gratissimum as a modulator of nicotine-induced free radical generation, lipid-protein damage and antioxidant status in important immune cell, peritoneal macrophages.